Anti-diabetic potential of stenochlaena palustris and diplazium esculentum - Daud, Dzulsuhaimi; Mat-Said, Zahid; Faizal, Nur Aisyah Munirah; Abdul-Rahman, Nur Fara Ellyana; Mohamad-Suaib, Nur Maizatul Husna; Tawang, Alene (2025)
The increasing global prevalence of diabetes mellitus highlights the urgent need for alternative therapeutic strategies that are affordable, effective and associated with minimal side effects. This study aimed to comparatively assess the anti-diabetic potential of Stenochlaena palustris and Diplazium esculentum ethanolic extracts through phytochemical screening and in-vitro bio-assay. The crude ethanolic extracts of both ferns were subjected to standard qualitative phytochemical analysis and anti-diabetic activity was evaluated using a-glucosidase inhibition assay. Both S. palustris and D. esculentum extracts demonstrated the presence of bioactive phytochemicals, with flavonoids, phenolics, saponins and tannins compounds being dominant. Comparative enzyme inhibition assay revealed that S. palustris and D. esculentum demonstrate moderate and comparable a-glucosidase inhibitory activity. It can be concluded that S. palustris and D. esculentum possess promising antidiabetic potential. Further in-vivo and animal trials are warranted to validate their efficacy and safety as phytopharmaceutical candidates.